Breastfeeding challenges and support in a high initiation population - Deena R. Zimmerman; Michael Kaplan; Hanna Shoob; Marlaina Freisthler; Monique Toledano; Chen Stein-Zamir (BMC, 2022)
Abstract Background The breastfeeding initiation rate in Israel is approximately 90%, yet exclusive breastfeeding drops sharply in the early postnatal period. The study objective was to assess early postpartum professional breastfeeding support, its association with breastfeeding success and identification of risk factors for early breastfeeding discontinuation. Methods As part of a post-discharge newborn follow-up study, a convenience sample of 868 mothers attending Maternal and Child Health Centers (MCHCs) up to three months post-partum were interviewed using a 26-item questionnaire. Breastfeeding-related questions covered demographic variables, pregnancy and birth details; breastfeeding duration, lactation support in hospital and post-discharge; and problems experienced. Results Most mothers, 797 (91.8%), initiated breastfeeding in hospital. All women who initiated breastfeeding in the hospital reported exclusive breastfeeding; by two weeks postpartum, 70 women (13.2%) were supplementing with formula (partial breastfeeding). Kaplan-Meier Survival Analysis revealed an estimated mean duration of exclusive breastfeeding in the sample population of 66.8 ± 1.5 days. This duration was shorter for women with preterm births, low birthweight infants (LBW), cesarean births, and hospitalizations in neonatal intensive care units (NICU). A total of 472 (59.3%) breastfeeding mothers reported receiving in-hospital guidance. Of these, 290 (61.3%) were observed breastfeeding. Of all women who initiated breastfeeding, 280 (35.1%) attended MCHC follow-up within 72 h of hospital discharge. A higher proportion of women experiencing breastfeeding difficulties attended an MCHC within 72 h (131/297, 44.1%) compared to women not experiencing difficulties (148/499, 29.7%). The most frequently reported problems were mechanical (55.2%) or milk supply concerns (18.5%). First-time mothers were more likely to report problems, as were Jewish (vs Arab) mothers. Conclusions Even in a population with high initiation rates of breastfeeding, breastfeeding duration, both exclusive and partial, is less than recommended. As much of this drop-off occurs during maternity leave, it is likely related to breastfeeding challenges other than employment. Breastfeeding support needs of women are currently not adequately met; staffing and time for both in-hospital and community-based counseling needs to be funded as well as mandated. Counseling hours should be tailored to assure adequate coverage of high-risk groups such as women after cesarean delivery and newborns requiring intensive care.